2021
DOI: 10.51847/cu6kx0jde3
|View full text |Cite
|
Sign up to set email alerts
|

Study of Wound-Healing Ointment Composition based on Highly Dispersed Zinc Oxide Modified with Nanoscale Silver

Abstract: A complex modern study of the ratio effect of components of an ointment composition based on highly dispersed Zinc oxide modified with nanoscale silver on its physical and chemical properties is performed. It was found that at a concentration of glycerol equal to C = 10%, and at a concentration of methylcellulose C = 3%, the value of the active acidity of the ointment composition is optimal (pH = 6.5-7). Studies of the structural and mechanical properties of the ointment composition have shown that the wound-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…To obtain the hydrogels, we considered the properties of the components, respectively, and the general methods of preparation of the hydrophilic gels. We considered the consistency (viscosity increasing) agents -carbopole 940 -dispersed in the vehicle using propylene glycol and ethyl alcohol as dispersing agents [40].…”
Section: Resultsmentioning
confidence: 99%
“…To obtain the hydrogels, we considered the properties of the components, respectively, and the general methods of preparation of the hydrophilic gels. We considered the consistency (viscosity increasing) agents -carbopole 940 -dispersed in the vehicle using propylene glycol and ethyl alcohol as dispersing agents [40].…”
Section: Resultsmentioning
confidence: 99%
“…There are works on the study of the venom activity of migalamorphic spiders [21], which concluded that the polypeptide combinations of the studied poisons have strong antiviral activity. The effect of other biologically active substances on antiviral activity has also been studied [22][23][24][25][26][27][28][29][30]. It is also worth noting the development of digitalization technologies [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Universal computer network technologies do not allow combining different types of medical equipment [21][22][23][24][25]42]. Therefore, its manufacturers were forced to develop their communication interfaces.…”
Section: Introductionmentioning
confidence: 99%